Halal logistics resources,capabilities and strategies for sustainabillty: An exploratory. - Karia, Noorliza (Universiti Sains Malaysia, 2017)
The need to implement halal business prescribed in the Quran has been acknowledged. Yet, there is few research and literature in halal, halal business/service and the interest in the halal logistics research is almost non-existent. A study on the halal service that focuses on the third-party logistics (3PLs) is therefore,crucial.